AquaNet - Automatic sensors from Bolmen AquaNet platform - Bolmen Research Station (Sweden Water Research, 2020)
Automatic sensor data from the AquaNet mesocosm facility.
Bolmen Research Station (2020). AquaNet - Automatic sensors from Bolmen AquaNet platform, 2017-08-22–2017-09-20 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/DwvfqFLlLl6Ljz7BZFCNzMxE
Keywords: SITES AquaNet; Chlorophyll; Dissolved oxygen; Photosynthetically active radiation; Turbidity; Time instant; Time instant; Photosynthetic Photon Flux Density; Photosynthetic Photon Flux Density; Water temperature; Water temperature; Chlorophyll a; Chlorophyll a; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap